CFP board anonymous case histories: Ethical themes of compensation disclosure. Issue 3 (28th October 2021) - Sensenig, Derek J.; Lurtz, Meghaan; Joseph, Mindy; Harris, Josh; White, Kenneth J.; McCoy, Megan
Abstract: This study analyzed the CFP® Board's anonymous case histories (ACH) for the ethical use and misuse of compensation disclosures on the CFP Board's "Find A CFP Professional" tool. More specifically we explored the research question: what are the characteristics of CFP professionals who have violated established ethical standards regarding fee‐only, fee‐based, and commission fee structures from 2009 to 2020 according to the theory of fraudulent ethical behavior? A thematic analysis was used to compare cases in which CFP certificants incorrectly characterized their compensation structure ( n = 23). Four themes emerged: practitioner characteristics, firm characteristics, payment characteristics, and culpability. Each theme was examined under the fraud pentagon's theoretical framework (Crowe, 2011). Several interesting findings emerged from the study, including tenured professionals representing a larger proportion of planners who committed ethics violations than previous research would suggest. In addition, there appeared to be difficulties understanding the fee‐only structure when working under certain licenses or firm structures. These findings support the need to maintain public disclosure of fee‐structure for consumers, highlights the importance of educating consumers on the differences between compensation types, and reinforces the need for continued education for CFP professionals to stay abreast of compliance matters.